Identification of Body Size and Body Shape of Garut Sheep Fighting Type and Meat Type and Garut Cross Based on Principal Component Analysis - Gunawan, A; Mulyono, RH; Sumantri, C (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2009)
This research was done to identify the body size and shape among three types of local sheeps of Garut fighting type, Garut meat type and their crossbred fighting and meat type in Garut district (Margawati, Sukawening and Wanaraja) and Bogor district (Ciomas and Cinagara). The total number of sheep from Garut district used in this study were 520 head consisting of crossbred sheep from Margawati (71 head), fighting sheep from Wanaraja (79 head), meat sheep from Wanaraja (84 head), fighting sheep from Sukawening (87 head) and meat sheep from Sukawening (62 head). Whereas the total number of sheep from Bogor district were 137 head consisting of those of fighting sheep from Ciomas (66 head) and from Cinagara (70 head). Some body measurenments measured in this study were body weight, body length, wither height, chest width, chest circumfrence, cranium, tail length and tail width. Analysis of all those sizes were based on principal component analysis (PCA) then visualized into the group of crowded diagram. Different group of crowed builded on the base of scoring in body size and body shape derivated from covarian matrix were able to identifed morphologycal penotypic differences among garut sheep studied. The results from canonical analyses showed that body lenght, chest girth,chest width, and wither height were the most discriminant variables had impact to the diferences score size between types of Garut sheep. However, the tail length and tail width were variables had impact to diferences score shape. The crowed diagram showed that an intersection among three types (fighting, meat and crossbred) of sheeps suspected as resulted from the same genetic resource, namely Garut sheep. Genetic flow was suspected from crossbred in Margawati to meat sheep in Cinagara as well as the sheeps from Sukawening and Wanaraja to fighting sheep in Ciomas. Close genetic distances that were found among fighting and meat sheeps in Sukaweining as well as fighting and meat sheeps in Wanaraja could be considered that these two groups of sheeps as the genetic resource of fighting sheep in Ciomas. (Animal Production 11(1): 8-14 (2009) Key Words: garut sheep, principal component analysis (PCA), body size and shape